MORPHOLOGICAL CHARACTERISTICS OF COMMERCIAL VALUE SEA-CUCUMBERS IN VIETNAMESE WATERS - Ho, Dao Tan (Vietnam Journal of Marine Science and Technology, 2006)
MORPHOLOGICAL CHARACTERISTICS OF COMMERCIAL VALUE SEA-CUCUMBERS IN VIETNAMESE WATERS